2015
DOI: 10.1002/pola.27592
|View full text |Cite
|
Sign up to set email alerts
|

Functional dye as a comonomer in a water‐soluble polymer

Abstract: In many applications, a functional additive is blended into a polymer matrix to enhance its properties. However, when the polymer and functional additive are applied to a surface, the functional molecule may be easily lost. In favorable cases, it may be possible to incorporate the additive directly into the polymer as a comonomer. In this study, a functionalized polymer has been obtained through the combination of linking a photodynamic, antimicrobial dye, Rose Bengal, to vinyl benzyl chloride via etherificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In vitro studies have been carried out to investigate the antibacterial effects of Cu ions from metallic copper surface [28] and Cu-containing nanoparticles. [12] Although many studies have reported the bactericidal mechanism of antibacterial nanomaterials and copolymers in the past few years, [2931] there have been very few reports about comprehensive mechanisms of the antibacterial effect of Cu ions. In the present study, Ti6Al4V5Cu with antibacterial activity was used to understand the antibacterial mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have been carried out to investigate the antibacterial effects of Cu ions from metallic copper surface [28] and Cu-containing nanoparticles. [12] Although many studies have reported the bactericidal mechanism of antibacterial nanomaterials and copolymers in the past few years, [2931] there have been very few reports about comprehensive mechanisms of the antibacterial effect of Cu ions. In the present study, Ti6Al4V5Cu with antibacterial activity was used to understand the antibacterial mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Fabrication of thin polymeric films has been of considerable importance in both industrial and fundamental research due to their potential applications in various areas, such as packaging, protective coatings, modern microelectronics, smart actuators, battery separators, antibacterial and antifouling films, biocompatible membranes for drug delivery, or tissue engineering . Among the methods used to design polymeric films, layer‐by‐layer (LbL) assembly strategy is very attractive due to its versatility and the large number of building‐blocks (synthetic and natural polyelectrolytes, inorganic nanoparticles, biomolecules, dyes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Development of protein therapeutics, including enzymes, antibodies, and cytokines, has attracted great attention from both academia and pharmaceutical industry [1][2][3][4][5][6][7][8][9][10]. Chinese hamster ovary (CHO) cells are widely used as the mammalian hosts for expression and production of therapeutic recombinant proteins due to the characteristics of high product quality, safety, and adaptability of suspension culture [11].…”
Section: Introductionmentioning
confidence: 99%